2016
DOI: 10.1007/s00429-016-1198-9
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity between the central nucleus of the amygdala and the bed nucleus of the stria terminalis in the non-human primate: neuronal tract tracing and developmental neuroimaging studies

Abstract: The lateral division of the bed nucleus of the stria terminalis (BSTL) and central nucleus of the amygdala (Ce) form the two poles of the ‘central extended amygdala’, a theorized subcortical macrostructure important in threat-related processing. Our previous work in nonhuman primates, and humans, demonstrating strong resting fMRI connectivity between the Ce and BSTL regions, provides evidence for the integrated activity of these structures. To further understand the anatomical substrates that underlie this coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 119 publications
7
76
0
Order By: Relevance
“…To reduce animal use, some of the injections placed in the amygdala and CEA (Study 2) were mapped as parts of other studies (Cho et al , 2013; Decampo and Fudge, 2013; Oler et al , 2016). All experiments were carried out in accordance with National Institute of Health guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce animal use, some of the injections placed in the amygdala and CEA (Study 2) were mapped as parts of other studies (Cho et al , 2013; Decampo and Fudge, 2013; Oler et al , 2016). All experiments were carried out in accordance with National Institute of Health guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Classic tracing studies showed that VA fibers project through the SLEA region of the substantial innominata, directly connecting the Ce to the BST (Novotny, 1977). In parallel, the ST exits the caudal amygdala to arch dorsally and rostrally over the thalamus, carrying with it a second set of projections from the Ce to BSTL (Klingler and Gloor, 1960;Freese and Amaral, 2009;Oler et al, 2016b). More recent tracing and diffusion imaging studies in monkeys have not only confirmed that the Ce and BSTL are structurally interconnected via these two direct pathways (primarily Ce ¡ BSTL) but have also identified a novel indirect pathway in the SLEA (Ce 7 SLEA 7 BSTL) (deCampo and Fudge, 2013;Oler et al, 2016b).…”
Section: The Central Extended Amygdala Is Tightly Interconnected and mentioning
confidence: 99%
“…In parallel, the ST exits the caudal amygdala to arch dorsally and rostrally over the thalamus, carrying with it a second set of projections from the Ce to BSTL (Klingler and Gloor, 1960;Freese and Amaral, 2009;Oler et al, 2016b). More recent tracing and diffusion imaging studies in monkeys have not only confirmed that the Ce and BSTL are structurally interconnected via these two direct pathways (primarily Ce ¡ BSTL) but have also identified a novel indirect pathway in the SLEA (Ce 7 SLEA 7 BSTL) (deCampo and Fudge, 2013;Oler et al, 2016b). In both monkeys and humans, the Ce and BST also show persistently high levels of physiological coupling Avery et al, 2014;Birn et al, 2014;Torrisi et al, 2015;Oler et al, 2016b), suggesting that they represent an evolutionarily conserved functional circuit.…”
Section: The Central Extended Amygdala Is Tightly Interconnected and mentioning
confidence: 99%
“…Both BNST and amygdala are strongly interconnected on a structural level (Sah, Faber, Lopez De Armentia, & Power, ; Waraczynski, ). The BNST is connected to the amygdala via the ventral amygdalofugal pathway and the stria terminalis (Sun, Roberts, & Cassell, ) and thus shows structural connections to the LB, CM, and SF (Cooke & Simerly, ; Oler et al, ; Weller & Smith, ). Particularly, the CM and the BNST have been proposed to belong to the medial extended amygdala due to their high similarity with respect to embryological origin, cell type, afferent, and efferent connections (Bienkowski & Rinaman, ; Bupesh, Abellán, & Medina, ; Dong, Petrovich, & Swanson, ; Sah et al, ) and timing of impulses to the brainstem (Nagy & Paré, ).…”
Section: Introductionmentioning
confidence: 99%